(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article explores the ethical dimensions of regulating artificial intelligence (AI) from a legal standpoint. It examines the implications of AI regulation on fairness, privacy, and access to justice within the legal context. Through analyzing existing legal frameworks, the author suggests strategies for addressing ethical concerns arising from the deployment of AI technologies by legal professionals.